Sustainable water use on the basis of regulation of water consumption, water disposal, wastewater quality at dairy production enterprises - Zakharko, Palina N.; Dubianok, Sniazhana A. (Journal of the Belarusian State University. Ecology, 2022)
Dairy industry enterprises are characterized by a frequent change in the types of products produced, which affects water use and the qualitative composition of wastewater generated on the territory of the enterprise. Due to the specifics of the implementation of technological processes for the production of products, the volumes of water disposal often exceed the volumes of water consumption by up to 30%, which is an important factor that must be taken into account when designing wastewater treatment plants at dairy industry enterprises (often designers equate the volumes of water disposal to the volumes of water consumption). The qualitative composition of wastewater varies greatly during the day and directly depends on the types of products produced. One of the ways of sustainable water use at enterprises is the constant planning of water consumption and wastewater disposal in conjunction with the volumes and types of products produced, the qualitative composition of wastewater. From a scientific point of view, forecasting water use, the qualitative composition of wastewater is possible by establishing spatio-temporal relationships between the types of products produced, volumes of water consumption and wastewater disposal, and the qualitative composition of wastewater at enterprises for the production of dairy products. In a number of localities of the Republic of Belarus, enterprises for the production of dairy products are city-forming, they develop and increase production, expand the range of products, which leads to an increase in the load on municipal treatment facilities in the locality. As a result, such enterprises, when expanding their production capacities, tend to organize a full cycle of wastewater treatment with their subsequent discharge into water bodies. For the last 5 years, there has been a stable dynamics of an increase in the anthropogenic load on water bodies by enterprises producing dairy products: annually 1-2 enterprises organize the release of wastewater after treatment facilities into a water body. Taking into account the emerging trends in water use, establishing relationships between the types of products produced, the volumes of water consumption and wastewater disposal, and the qualitative composition of wastewater will allow enterprises producing dairy products to predict water use and wastewater quality.
Keywords: water consumption; water disposal; spatio-temporal dependencies; quality; wastewater; dairy industry